2013
DOI: 10.1039/c3dt50406a
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional iron-chelators with protective roles against neurodegenerative diseases

Abstract: The multifactorial nature of Alzheimer's disease (AD), and the absence of a disease modifying drug, makes the development of new multifunctional drugs an attractive therapeutic strategy. Taking into account the hallmarks of AD patient brains, such as low levels of acetylcholine, misfolding of proteins and associated beta-amyloid (Aβ) aggregation, oxidative stress and metal dyshomeostasis, we have developed a series of compounds that merge three different approaches: metal attenuation, anti-Aβ aggregation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 49 publications
1
45
0
1
Order By: Relevance
“…30 The IC 50 values for AChE inhibition are summarized in Table 1 35 this feature is expected to reduce the cholinergic-induced aggregation of the Aβ peptide, and thus enhance the overall anti-Aβ aggregation ability of these multifunctional hybrid compounds (see below).…”
Section: Ache Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The IC 50 values for AChE inhibition are summarized in Table 1 35 this feature is expected to reduce the cholinergic-induced aggregation of the Aβ peptide, and thus enhance the overall anti-Aβ aggregation ability of these multifunctional hybrid compounds (see below).…”
Section: Ache Inhibitionmentioning
confidence: 99%
“…Cell reduction ability as a surrogate of cell viability was measured by using a quantitative colorimetric assay with MTT according to the method of Mosmann (1983). 30,50 In brief, cells…”
Section: Cell Treatments and Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…15 The assay solution contained 374 tL of Hepes buffer (50 mM and pH8.0), a variable volume (10- To study the A342 aggregation inhibition, a reported method, based on the fluorescence emission of thioflavin T (ThT), was followed. 16,28,29 It is based on the assumption that …”
Section: Acetylcholinesterase Activitymentioning
confidence: 99%
“…14,15,16 Very recently, the conjugation of tacrine (TAC) with S-allylcysteine (SAC) and S-propargylcysteine (SPRC), two natural based products with neuroprotective and antioxidant roles (e.g. garlic derivatives), 17,18 resulted in a set of bihybrids (TAC-SAC and TAC-SPRC) with important neuroprotecting properties which, besides the expected AChEI and anti-oxidant properties, presented also inhibitory activity for the self-and Cuinduced Af3 aggregation.…”
Section: Introductionmentioning
confidence: 99%